Analisis Pengaruh Rasio LDR, GCG, NIM dan CAR Terhadap Profitabilitas Pada Perusahaan Perbankan yang Terdaftar dalam Indeks Kompas 100 Pada Tahun 2012-2015 - B41112034, Rangga Dwi Prasetya (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
ABSTRACT Â This study aims to analyze the effect of the ratio RGEC (Risk Profile, Good Corporate Governance, Earnings and Capital) to the profitability of banking companies listed in Kompas Index 100 either partially or simultaneously. This study uses the ratio of Loan to Deposit Ratio (LDR) on aspects of risk profiles, Good Corporate Governance (GCG), the ratio of net interest margin (NIM) in the aspect of profitability, and the ratio of Capital Adequacy Ratio (CAR) capital aspect. The population of this research is all the banks listed on Kompas Index 100 from 2012 until 2015. The total samples are 9 banks that have been determined through purposive sampling. Data analysis will be performed with the classical assumption and hypothesis testing with multiple linear regression method. The results show that partially, LDR has negative and significant influence towards ROA, GCG has positive but insignificant influence towards ROA, NIM has positive and significant influence towards ROA and CAR has positive but insignificant influence towards ROA. Simultaneously, this study stated that the LDR, GCG, NIM and CAR have significant influence towards ROA in the amount of 39,3% and the balance of 60,7% is explained by other variables. Keywords: ROA (Return On Assets), LDR (Loan to Deposit Ratio), GCG (Good Corporate Governance), NIM (Net Interest Margin), CAR (Capital Adequacy Ratio), IDX ( Indonesian Stock Exchange).